Identifikasi Potensi Lokal di SMA Negeri 1 Pemenang sebagai Dasar Penyusunan Lembar Kerja Peserta Didik (LKPD) Biologi Kelas X - Kurniati, Eni; Nurhidayati, Siti; Efendi, Ismail (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Local potential has meaning as a source or strength possessed by each region to be utilized in certain activities. The local potential that has been utilized in biology learning is the school yard area as a place for learning practices. The aims of this study are: 1) to identify what local potentials exist in SMA Negeri 1 Pemenang, North Lombok Regency; and 2) find out how to develop local potential in SMA Negeri 1 Pemenang, North Lombok Regency as the basis for the preparation of class X Biology LKPD. This type of research is descriptive research and development research. The development model used is a 4D development model which is modified into 3D, namely Define, Design, and Develop. The location used as a place of research is a live pharmacy, where a live pharmacy has several types of medicinal plants that are used as learning media. Based on the validation results from the validator, the results from linguists were 67.5%; material experts by 57.5%; and expert display by 42.5%; with an average of 55.5% in the eligibility category the Student Worksheet is quite valid.